2006
DOI: 10.1097/01.psy.0000244025.20549.bd
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Depression, Prenatal Anxiety, and Spontaneous Preterm Birth: A Prospective Cohort Study Among Women With Early and Regular Care

Abstract: These findings provide evidence that antenatal depression is significantly associated with spontaneous preterm birth in a population of European women receiving early and regular care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
3
17

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(218 citation statements)
references
References 46 publications
13
185
3
17
Order By: Relevance
“…[7][8][9][10] A number of anatomical, physiologic/hormonal and stress factors may be implicated in hindering successful lactation, for example, immature mammary development resulting from shortened gestation (lactogenesis I), decreased milk production (lactogenesis II), and/or stress. 8,[11][12][13][14][15] Stress, be it physical or psychological, may hinder lactation via physiologic/hormonal responses that inhibit milk synthesis (for example, prolactin), milk release (for example, oxytocin) and/or maternal behavior. 16 The stress that mother's experience, following a premature delivery, may include not only maternal concerns over infant's health, 8,17,18 but also their own health, lifestyle (for example, employment, family responsibilities), lack of social support and/or limited socioeconomic resources, just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] A number of anatomical, physiologic/hormonal and stress factors may be implicated in hindering successful lactation, for example, immature mammary development resulting from shortened gestation (lactogenesis I), decreased milk production (lactogenesis II), and/or stress. 8,[11][12][13][14][15] Stress, be it physical or psychological, may hinder lactation via physiologic/hormonal responses that inhibit milk synthesis (for example, prolactin), milk release (for example, oxytocin) and/or maternal behavior. 16 The stress that mother's experience, following a premature delivery, may include not only maternal concerns over infant's health, 8,17,18 but also their own health, lifestyle (for example, employment, family responsibilities), lack of social support and/or limited socioeconomic resources, just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the notion that the developmental delays were a consequence of early delivery brought on by maternal antenatal depression. Results from several studies substantiate the impact of maternal depression on the length of gestation by showing that antenatal depression is associated with either a reduced gestational age [37] or a greater incidence of preterm birth among severely depressed women compared to non-depressed women [38,39]. The influence of antenatal depression on gestational age may be explained by a potential biological pathway.…”
Section: Antenatal Depression Gestational Age and Infant Mental Devementioning
confidence: 71%
“…The influence of antenatal depression on gestational age may be explained by a potential biological pathway. According to recent studies, cortisol increases the release of a placental corticotropin-releasing hormone (CRH) [39,40], which plays a key role in triggering parturition [40][41][42][43]. Antenatal depression is related to a greater incidence of premature delivery and to elevated antenatal cortisol levels compared to non-depressed women [38].…”
Section: Antenatal Depression Gestational Age and Infant Mental Devementioning
confidence: 99%
“…A study analyzing the anxiety of 634 French pregnant women through SAIT has found an average state of anxiety during the 20 th and 28 th week of gestation (5) . which helps to eliminate the effects caused by tension (10) .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of anxiety during pregnancy is associated with adverse perinatal results, particularly preterm births and low birth weight, and there is also a risk for developing emotional problems in children (5,16) .…”
Section: Controlmentioning
confidence: 99%